Reserve metabolism of stored and germinated Araucaria angustifolia seeds - Araldi, Cristhyane Garcia (2019)
Germination metabolism of recalcitrant seeds of Araucaria angustifolia is activated in storage, which complicates the seeds conservation and utilization. This study aimed to identify the changes in the reserve metabolites of A. angustifolia seeds throughout storage in order to understand the processes of hydrolysis caused by germination metabolism. Mature seeds were harvested in southern Brazil and stored in an ambient environment and cold chamber conditions. Biochemical analyses were performed for embryos and megagametophytes from seeds stored for 0, 15, 30, 45, and 90 days. Due to seeds being in advanced germination in storage, they were evaluated at 90 days in different early developmental categories: I – seeds with mature embryos, II – seeds with embryos showing apparent elongation along the embryonic axis, and III – seeds with root protrusion. Higher contents of carbohydrate, protein, and amino acids were observed in embryos compared to megagametophytes, and these metabolites were decreased after onset of germination, especially in the embryo tissue. Mobilization of metabolites in megagametophytes would probably increase in later stages of germination. It is suggested that such alterations are not due to deterioration of reserve components, but instead are based on seed metabolism, which remains active after harvest with hydrolysis of metabolites providing energy for germination.